Cityscape Under the Gaze of Migrant Women: The Reimagination of Urban World in Vietnamese Independent Films - Hoang, Cam Giang (Journal of Urban Culture Research, 2023)
In Vietnam, since the Reform era (1986) and the government’s firm urbanization policy, replacing the pre-1986 discourse of the countryside as the Garden of Eden, a myth of the city as a place of endless pleasure has been gradually built up in mass media. As a result, the urban spectacle has become the ideal symbol of the speed of development, national strength, and masculinity in state-sponsored and commercial movies/dramas. Meanwhile, through the ‘slow cinema,’ independent female directors such as Siu Pham, Nguyen Hoang Diep, Bui Kim Quy, Pham Hoang Minh Thy, and Pham Nhue Giang have questioned the ‘urban fantasy’ from the standpoint of those who are twice marginalized in the city space: the poor female immigrants. In films from these directors, women suffer slow violence from polluted, substandard living environments and endure gender prejudice and abuse in cities. From that, those films present a new strategy of social justice in contemporary Vietnamese urban areas: ecological justice is associated with gender equity and visual equity.